GCAD TECH PROFILE WEBSITE USER EXPERIENCE DESIGN USING THE GOAL DIRECTED DESIGN METHOD - Teguh Rijanandi; Mohammad Fikri Nur Syahbani; Rahmat Dian Rifa'i; Irsyad Zulfikar; Anggeralmasih Wiradika Rusmana; Tri Dimas Cipto Satrio Wibowo (Jurnal Teknoinfo, 2023)
GCADTech is a company engaged in services such as CAD engineers, CNC Programming, Mold Making, 3D Printing, 3D Scanning and training regarding manufacturing. GCADTech has a desire to develop its company by creating a profile website that aims to make it easier for the public or internet users who need services in the manufacturing sector. The purpose of this writing is to produce a design for the appearance of the GCADTech website which uses the Goal-Directed Design method, which consists of six stages. The first is research to find out what needs are needed for making a website. Both modeling models the research results into the form of a user persona. The three requirements are specifications of what must be implemented. Fourth, namely the design framework, At this stage, the website interface design is carried out. The fifth is refinement, this stage is working on the user interface to become a mockup with a high-fidelity level. The six design supports that create an analysis of the results of prototype testing with the user experience questionnaire (UEQ). The results of the UEQ assessment on the website display get Above Average on all scales.